Application Areas and Development Prospects of Nanomedicine - Jena, Aujjwalya Kumar; Panigrahi , Rajashree (International Journal of Psychosocial Rehabilitation, 2019)
Nanotechnology has become a focus for scientific research and technological development along with related concepts such as nanomaterials, nanostructures and nanoparticles. Nanotechnology, that is, the development and use of nanometer-scale materials and tools, already has various applications in the electronics and other areas. The highest hopes, though, are for its use in biotechnology and in medicine, with direct impact both could have on health outcomes of future societies. The emerging nanomedicine discipline is bringing together nanotechnology and medicine to develop novel therapies and improve existing treatments. The atoms and molecules are engineered in nanomedicine to create nanostructures of the same size as biomolecules for contact with human cells. Through activating the body’s own repair mechanisms, this technique offers a range of innovative medical approaches and "smart" therapies. It will improve early diagnosis and treatment of diseases like cancer, Alzheimer’s, diabetes, cardiovascular and Parkinson’s disorders. Preventive pharmaceutical drugs can then become a reality.